PROFILING AND IDENTIFYING INDIVIDUAL USERS BY THEIR NATURAL LANGUAGE USAGE FOR POSITIVE IDENTIFICATION - Darusalam, Darusalam; Cholil, Widya (Universitas Bina Darma, 2012)
Profiling and identifying individual users is an approach to help recognize intrusions in a computer system. User profiles are important in many applications since they record highly user-specific information - profiles are basically built to record information about users or for users to share experiences with each other. Thus, user profiles are used to aggregate relevant information about a userâs activities, and to identify patterns in their behavior. This research uses the n-gram analysis method for characterizing each userâs style, and can potentially provide accurate user identification. As a result, n-gram analysis of a users typed inputs offers another method for intrusion detection as it may be able to both positively and negatively identify users. The contribution of this research is to assess the use of a userâs writing styles in both natural language as a user profile characteristic that could enable intrusion detection where intruders masquerade as real users. Keywords: User Profiling, Identification, Computer Security, Anomaly Detection